Market integration for selected vegetables in southwestern Nigeria - Adeoye, I.; Dontsop Nguezet, Paul M.; Amao, I.; Fajimi, F. (Informa UK Limited, 2013)
The absence of market integration has important implications for market efficiency. An integrated vegetable market will permit low spatial and intertemporal variation in prices, implying that commodity market prices will be functionally related. Vegetables are important sources of nutrients and income. The study assessed market integration between urban and rural markets of Amaranthus cruentus L, Corchorus olitorius L, and okra [Abelmoschus esculentus (L.) Moench] in South-western Nigeria. Data on monthly prices from 2004 to 2009 was collected from the Oyo State, Nigeria, Agricultural Development Project. Data were analyzed using augmented Dicker-Fuller and Granger causality tests and the index of market connection (IMC). Prices of A. cruentus and C. olitorius were stationary at its level, and the price of okra was stationary by the first difference. Johansen co-integration analysis indicated that rural and urban vegetable market prices are co-integrated and form part of the same market, indicating a flow of market price information. The Granger causality test suggested that urban and rural prices of Corchorus have a causal relationship. Rural okra and C. olitorius exhibited a bidirectional causal relationship. The IMCs for Amaranthus, Corchorus, and okra were 0.64, 0.26, and 3.32, respectively, indicating that Amaranthus and Corchorus markets exhibit high short-run market integration, whereas okra exhibited low short-run market integration. There is quick transmission of prices between urban and rural markets for Amaranthus and Corchorus, whereas there is slow transmission of prices between urban and rural markets for okra because the flow of information regarding okra prices is not efficient. The policy implication of the study is that market price information should be made available to farmers through various agricultural programs and a market infrastructure including transportation and communication facilities should be developed.